ANALYSIS OF THE PERFORMANCE OF APRON MOVEMENT CONTROL (AMC) PERSONNEL ON PASSENGER ORDERS AT THE APRON OF HUSEIN SASTRANEGARA BANDUNG INTERNATIONAL AIRPORT - Subroto, Ariyo; Candra Yuniar, Dwi; Parjan, Parjan; Komalasari, Yeti (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
This research was conducted to determine the performance of Apron Movement Control (AMC) personnel on passenger order at the apron of Husein Sastranegara International Airport Bandung and to find out how passenger order at the apron of Husein Sastranegara International Airport Bandung. Supervision of order and safety at the apron is a task that must be carried out by Apron Movement Control (AMC) personnel. There are still passengers who do not comply with the markings to cross the apron of Husein Sastranegara International Airport Bandung when getting off or boarding from an airplane can have a major impact on safety. This happens because the supervisory function carried out by Apron Movement Control (AMC) personnel is not optimal. This research uses descriptive qualitative methods with data collection techniques are observation, interviews and literature studies. The results of this study indicate that the performance of Apron Movement Control (AMC) personnel at Husein Sastranegara International Airport Bandung still has to be improved, this can be indicated by the still found problems of order of passengers boarding and disembarking from aircraft that endanger flight safety and security at Husein Sastranegara International Airport Bandung. Success indicators were obtained to reduce passenger disorder in the apron in the form of optimizing digital banners, adding signage and reoperating the apron bus.